2023
DOI: 10.3390/ma16186258
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Development of a Way to Modify Asphalt Mixtures with PET Recyclates

Tomasz M. Majka,
Krzysztof Adam Ostrowski,
Marcin Piechaczek

Abstract: Due to the growing need to recycle plastics, new possibilities for their reuse are intensively sought. In the Asian market, waste polymers are increasingly used to modify road bitumen. This solution is beneficial in many aspects, especially in economic and ecological terms. In this work, recycled poly(ethylene terephthalate) (RPET), obtained from storage points located in Lesser Poland, was subjected to material recycling, and its properties were examined using three analyses: differential scanning calorimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…An excessive PET content reduces bitumen ductility. An increase in the PET content improves the stiffness and viscosity of bitumen and bituminous mixes [27,28]. Studies on PET implementation showed no evident mix stability losses or adverse impacts on the BBR critical temperature when the PET content was up to 6% [29].…”
Section: Introductionmentioning
confidence: 98%
“…An excessive PET content reduces bitumen ductility. An increase in the PET content improves the stiffness and viscosity of bitumen and bituminous mixes [27,28]. Studies on PET implementation showed no evident mix stability losses or adverse impacts on the BBR critical temperature when the PET content was up to 6% [29].…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have evaluated the effects of using recycled PETE as a modifier of the asphalt binder on the rheological properties of the modified binder [11][12][13][14][15][16][17][18][19]. Polyethylene terephthalate, commonly abbreviated as PET, PETE, or the obsolete PETP or PET-P, is the most common thermoplastic polymer resin of the polyester family and is used in fibers for clothing (>60%) and containers for liquids and foods (30%).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, there is increasing interest currently in using recycled PETE as a modifier of the asphalt binder to enhance its physical and rheological properties, especially the rutting performance of the modified binder [11,13,17], and improving the properties of asphalt mixtures and their resistances to rutting and fatigue cracking [12,19]. Also, there is increased potential in the current state-of-the-art uses of recycled PETE in the asphalt binder and asphalt mixtures from an environmental perspective to help in recycling waste plastic materials and reduce the environmental concerns related to the increasing quantities of these waste materials and the conventional ways for disposing of them [14,15,18].…”
Section: Introductionmentioning
confidence: 99%